Early growth response 1 transcription factor and its context-dependent functions in glioblastoma - Rasras, Saleh; Akade, Esma’il; Mohammadianinejad, Seyed Ehsan; Barahman, Maedeh; Bahadoram, Mohammad (Contemporary Oncology/Współczesna Onkologia, 2024)
Glioblastoma is the most aggressive form of primary brain tumour in adults. This tumour employs numerous transcription factors to advance and sustain its progression. Current evidence suggest that early growth response 1 (EGR1) plays a dual role as both an oncogene and a tumour suppressor in glioblastoma. Early growth response 1 expression is prevalent in glioblastoma, affecting over 80% of cases. Early growth response 1 regulatory roles extend to angiogenesis, cell adhesion, and resistance to chemotherapy, notably influencing pathways like hypoxia-inducible factor 1 and vascular endothelial growth factor A. Early growth response 1 can also induce cell adhesion, migration, chemoresistance against temozolomide, stemness, and self-renewal in glioblastoma cells. Despite its oncogenic functions, EGR1 can also suppress tumours by upregulating non-steroidal anti-inflammatory drug-activated gene 1 and phosphatase and tensin homolog deleted on chromosome ten, and inhibiting invasion and metastasis. Additionally, EGR1 may have hypothetical implications in the viral hit-and-run theory, particularly regarding cytomegalovirus infection. The key findings of this review are the context- dependent nature of EGR1’s actions and its potential as a prognostic marker in glioblastoma. Further research is needed to understand EGR1’s role fully and exploit its potential in clinics.